Popularization interest in the care and protection of disabled- Rights pulmonary - Ahmed, Mohammed Sulaiman Al; Ahmed, Luqman Othman (Journal of Legal and Political Studies, 2014)
There is no doubt that the protections established by law for some groups in society do not have an end, as it shows the means and mechanisms whenever a new evolved life and have evolved with the perceptions of rights around the concept of human rights, the legislature change his priorities from time to time and from place to place due to change concerns legislative interference to regulate a particular issue. Today, the concern of legislators to the laws of social welfare in countries that have seen legislative development, is striking. This concern constitutes a firm persuasion on part of nations in their consideration for the importance of taking care of some groups in the society. Disabled people are among such groups who became disabled by losing one of their body parts, sometimes, because of their sacrifice or service to the public. The help of society to disabled people is approved by the international and national legitimacy, but we believe that the care and protection to this class need greater support, at least, as part of public interest and this is what we mean by (popularization). Such approach is approved by the basic human rights principles
Keywords: Protection; Human rights; Legislative; interference